Analysis of deletion breakpoints from 1,092 humans reveals details of mutation mechanisms - Abyzov, Alexej; Li, Shantao; Kim, Daniel Rhee; Mohiyuddin, Marghoob; Stütz, Adrian M.; Parrish, Nicholas F.; Mu, Xinmeng Jasmine; Clark, Wyatt; Chen, Ken; Hurles, Matthew; Korbel, Jan Oliver; Lam, Hugo Y. K.; et al. (Nature Communications, 2015)
Investigating genomic structural variants at basepair resolution is crucial for understanding their formation mechanisms. We identify and analyse 8,943 deletion breakpoints in 1,092 samples from the 1000 Genomes Project. We find breakpoints have more nearby SNPs and indels than the genomic average, likely a consequence of relaxed selection. By investigating the correlation of breakpoints with DNA methylation, Hi-C interactions, and histone marks and the substitution patterns of nucleotides near them, we find that breakpoints with the signature of non-allelic homologous recombination (NAHR) are associated with open chromatin. We hypothesize that some NAHR deletions occur without DNA replication and cell division, in embryonic and germline cells. In contrast, breakpoints associated with non-homologous (NH) mechanisms often have sequence microinsertions, templated from later replicating genomic sites, spaced at two characteristic distances from the breakpoint. These microinsertions are consistent with template-switching events and suggest a particular spatiotemporal configuration for DNA during the events.